Influence of Supplementing Solid State Fermented Biomass on Digestibility, Microbial Nitrogen Supply and Enteric Methane Emissions in Cattle - Sherasia, P.L.; Pandya, P.R.; Parnerkar, S.; Prajapati, M.V.; Murty, S. (Indian Journal of Animal Nutrition, 2018)
Present study was carried out to evaluate the effect of supplementing solid state fermented (SSF) biomass on nutrient intake, digestibility, rumen fermentation patterns, microbial nitrogen supply and methane emissions in crossbred cattle. Six non-lactating crossbred cattle (445.6 kg BW) were used in a replicated 3 Ã— 3latin square design. Animals in control group (T1) were fed total mixed ration (TMR) containing concentrates and wheat straw in 40: 60 ratio. Animals in group T2 were fed TMR containing concentrates, wheat straw and groundnut straw in 40: 30: 30 ratio whereas the animals in group T3 were fed TMR containing concentrates, wheat straw, groundnut straw and SSF biomass in a ratio of 40: 25: 30: 5. The intakes of nutrients and rumen parameters were not affected by the treatments. Digestibility coefficient of DM, OM, CF, NDF and cellulose improved by 8.9 (P